APPLICATION OF BUSINESS MODEL CANVAS IN PRODUCTION AND MARKETING OF SOLOG (ANALOGUE SAUSAGE) - Satriya Bayu Aji; Herlina Herlina; Bambang Herry Purnomo (Food ScienTech Journal, 2020)
Business Model Canvas (BMC) is an alternative option to create new business models. BMC includes customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structure. They are able to support companies aligning their business activities. By applying BMC, companies have several alternatives of business models. A research was conducted in order to apply BMC for Small Medium Enterprises (SMEs) in Jember Regency. The descriptive method was employed to arrange BMC, while the qualitative analysis was applied for data analysis. Primary data collection was obtained by customers’ interview. This paper describes the business plan of SOLOG (Analogue Sausage) product and application of BMC in the SMEs. The BMC creation for SOLOG was done in three stages. The first stage was a problem test, the second stage was a solution test and the last stage was verification model business. The last stage was chosen as the business model recommendation that is suitable as a reference in the business activities of SOLOG product.